Kajian Audit Keselamatan dan Kesihatan Pekerjaan terhadap aspek fizikal di Kolej Kediaman Dato’ Onn, UKM : study on occupational safety and Health Audit Of Physical Aspect at Dato’ Onn Residential College, UKM - Kadir A,; Kadaruddin A,; Shaharuddin A,; Azahan A,; Muhammad Rizal R,; Lukman ZM,; Azmi A,; Anuar I,; Nur Baiti MO, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2011)
Background: Safety and health audit study is a part of occupational safety and health risk assesment. Thus, student’s residential audit is important in order tu ensure the safety rules which implemented by the management is appropriate and follow the standard set forth. Furthermore, it also important to determine places, area or situation that might lead to hazard risk so that prevention step could be plan and implement. Objective: This study was to determine the safety level of students residential in physical aspects. Methods: Safety inspection or audit conducted is in accordance with criteria and indicators listed in the checklists that have been formed based on the audit forms from the Department of Safety and Health (DOSH), National Institute of Safety and health (NIOSH) and the Occupational Safety and Health Committee of UKMs (JKKP).Several indicators are also included in the audit form as to ensure it covers all the technical aspect and suited with the college conditions. The safety level for each of the blocks in KDO is categorized using points and percentage score obtained. Results: Based on the overall score, the average safety score in percentage for areas in KDO are preceded by general office with score 85.5% followed by residential blocks with 71.5%, facilities with score 71.2% and administration block with 70.9%. The results of the study show that most of the areas are at least in a safe level. Conclusion: Roles of employer and college administration, significant OSH programme and safety audit are important factors as to ensure the safety of student's residential college.